Experimental and Analytical Study on the Penetration of Corundum-Rubble Concrete Subjected to Projectile Impact - Y. L. Xue; D. G. Tang; W. X. Chen; Z. Z. Li; D. P. Li; M. L. Yao (Shock and Vibration)
A new type of composite concrete which can be called corundum-rubble concrete (CRC) was presented to improve the resistance of protective structure to the projectile impact. Comparative experiments were conducted between CRC and reinforced concrete, and a modified Taylor model was proposed to predict the penetration depth of CRC targets. Experimental results show that CRC is much higher than reinforced concrete in both strength and hardness and shows excellent resistance to the 0.125 m-diameter projectile impact. Theoretical analyses demonstrated that the modified Taylor model’s predicted results were in good agreement with the measured values.